(untitled) (Південний архів (історичні науки), 2023)
Vytautas Tower is a unique architectural structure that is a cultural heritage site of national importance. Since the beginning of the full-scale invasion of Ukraine by Russian troops, it has received special attention from historians, architects, and local historians. In addition, tourists, having absorbed the entire palette of information about the tower through videos and promotional brochures, made their own excursion routes to it. However, the tower gained much more resonance due to the construction of the Kakhovka hydroelectric power ІІ, which was to be located in close proximity to it. This prompted many researchers and enthusiasts to search for the historical context, origin, and purpose of the tower. Local history research, archaeological excavations, and historical research on the tower became popular and flooded the scientific space with various, often contradictory, information. The purpose of the article is to study all the available views on the issue of Vytautas Tower that are known to historical science today. This is not an attempt to support any of them. On the contrary, it is an attempt to point out the arguments of each researcher, to reveal the source base they use, and to comprehensively cover all versions of the origin, purpose, and historical context. At the same time, the author, based on historical sources, wants to put forward his own thesis on the purpose of the tower, which in the future will help to understand more specifically the purpose of its architectural structures and historical features. Various historical methods were used in the study. The comparative historical method was used to explain the historical context of the facts about the tower’s origin. The historical-systemic method was used to analyze the structure and functions of the tower, dynamic changes in its purpose and use in different historical periods. The result of the study is a consolidation of the entire spectrum of historical opinions and knowledge about the Witowt Tower in one article. In particular, about its medieval (Lithuanian) and modern origins, its defense, mill, and waterpressure purposes, and its historical context. The scientific conclusion of the article is that regardless of the historical context, age, and purpose, the tower is a unique architectural object that requires a detailed archaeological survey, historical study, and preservation.